Preparing Teachers for Rural Schools - John Guenther; Tom Weible (Journal of Research in Rural Education, 1983)
Evidence continues to mount indicating that rural/small schools face educational challenges not generalizable to their urban counterparts. This article discussesthe apparent neglectof rural schools and identifies some of the problems commonly associated with teaching in rural communities. The authors advance the need for preservice/inservice programs for rural teachers and suggest program components that may improve teacher competencie